Self-regulation "versus" regulation. Journalistic Discourse on the Proposition of Law Statute of the Professional Journalist (2004-2008) - Jiménez Gómez, Eva (Estudios sobre el Mensaje Periodístico, 2011)
This article is a synthesis of extensive research by the author and funded by Blanquerna Faculty ofCommunication. This paper analyzes the discourse of some journalists and media on the Proposition of Law Statute of the professional journalist from a normative perspective. To this end, we have used two main techniques: content analysis and a rhetorical one. The research, of a qualitative nature, pays particular attention to the arguments and the implicit ones underlying them. The analysis reveals the depth of differences, to the point where we can talk about opposing views and attitudes on the issue.